Discrimination, disadvantage and disempowerment during COVID-19: a qualitative intrasectional analysis of the lived experiences of an ethnically diverse healthcare workforce in the United Kingdom - Mayuri Gogoi; Irtiza Qureshi; Jonathan Chaloner; Amani Al-Oraibi; Holly Reilly; Fatimah Wobi; Joy Oghogho Agbonmwandolor; Winifred Ekezie; Osama Hassan; Zainab Lal; Anuj Kapilashrami; Laura Nellums; et al. (BMC, 2024)
Abstract Background Healthcare workers (HCWs) in the United Kingdom (UK) have faced many challenges during the COVID-19 pandemic, some of these arising out of their social positions. Existing literature explicating these challenges (e.g., lack of appropriate PPE, redeployment, understaffing) have highlighted inequities in how these have been experienced by HCWs based on ethnicity, gender or, job role. In this paper, we move a step ahead and examine how the intersection of these social positions have impacted HCWs' experiences of challenges during the pandemic. Methods We collected qualitative data, using interviews and focus groups, from 164 HCWs from different ethnicities, gender, job roles, migration statuses, and regions in the United Kingdom (UK) between December 2020 and July 2021. Interviews and focus groups were conducted online or by telephone, and recorded with participants' permission. Recordings were transcribed and a hybrid thematic analytical approach integrating inductive data-driven codes with deductive ones informed by an intersectional framework was adopted to analyse the transcripts. Results Thematic analysis of transcripts identified disempowerment, disadvantage and, discrimination as the three main themes around which HCWs' experiences of challenges were centred, based on their intersecting identities (e.g., ethnicity gender, and/or migration status). Our analysis also acknowledges that disadvantages faced by HCWs were linked to systemic and structural factors at the micro, meso and macro ecosystemic levels. This merging of analysis which is grounded in intersectionality and considers the ecosystemic levels has been termed as 'intrasectionalism'. Discussion Our research demonstrates how an intrasectional lens can help better understand how different forms of mutually reinforcing inequities exist at all levels within the healthcare workforce and how these impact HCWs from certain backgrounds who face greater disadvantage, discrimination and disempowerment, particularly during times of crisis like the COVID-19 pandemic.